EFFECTIVE ASPECTS OF ADVOCACY SERVICES AMONG LEGAL SERVICES - Turaev Shakhriyor Shodiyorovich (Scholar Express Journal, 2025)
This article, for the first time, reveals the theoretical and methodological foundations of advocacy services among legal services, opening up ways to develop advocacy services as a whole in the practical implementation of decrees and decisions issued in our rapidly developing country, implementing the tasks specified in the action strategy, creating new comprehensive promising directions. Advocacy activities are always available in accordance with the direct requirements of the Constitution, and mechanisms for increasing the effectiveness of advocacy services to provide qualified legal assistance to individuals and legal entities are described
Keywords: Legal service; among; advocacy services